The Influence of Fundamental Factors and Macroeconomics Against Dividend Payout Ratio and Company Value in LQ45 Non-Banking Registered Companies on the Indonesia Stock Exchange - Rudi Sanjaya; Krida Puji Rahayu (Kusuma Negara Business School, 2020)
This research aims to test and analyze the influence of Fundamental Factors and on Dividend Payout Ratio (DPR) and its impact on the company's value in the Company LQ-45 period 2014-2017. The data used is secondary data in the form of company financial statements obtained from the Indonesia Stock Exchange (IDX). A research sample of 19 companies that met the specified criteria. The data analysis method uses linear regression analysis and path analysis. The results of the data analysis show that ROE affects the Dividend Payout Ratio. DER, NPM, and Inflation have no effect on dividend payout ratios. ROE, NPM, and Inflation have no effect on the Company's Value. Debt to Equity Ratio Dividend Payout Ratio affects the Value of the Company. There is no indirect influence between ROE, DER, NPM, and Inflation on the Company's Value.